Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Our platform offers a seamless experience for finding reliable answers from a network of experienced professionals. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

Problem 4

Use the fundamental theorem of line integrals to evaluate
[tex]\[ \int_C \vec{F} \cdot d\vec{r} \][/tex]
for the vector field
[tex]\[ \vec{F}(x, y, z) = \langle 4x - 2y + 2z, -2x + 2yz + z^2, 2x + 2yz + y^2 \rangle, \][/tex]
where [tex]\( C \)[/tex] is the curve going from [tex]\( (1,0,2) \)[/tex] to [tex]\( (1,1,1) \)[/tex].

Show how you verified that [tex]\( \vec{F} \)[/tex] is conservative.


Sagot :

To solve the problem using the Fundamental Theorem of Line Integrals, we need to proceed through the following steps:

1. Verify if the vector field [tex]\(\vec{F}\)[/tex] is conservative.
2. Find the potential function [tex]\(f(x, y, z)\)[/tex] if the vector field is conservative.
3. Evaluate the potential function at the endpoints [tex]\((1, 0, 2)\)[/tex] and [tex]\((1, 1, 1)\)[/tex].
4. Calculate the line integral using the fundamental theorem for the conservative vector field.

---

### Step 1: Verify if the Vector Field is Conservative

A vector field [tex]\(\vec{F}(x, y, z) = \langle P, Q, R \rangle\)[/tex] is conservative if there exists a potential function [tex]\(f(x, y, z)\)[/tex] such that:
[tex]\[ \vec{F} = \nabla f = \left( \frac{\partial f}{\partial x}, \frac{\partial f}{\partial y}, \frac{\partial f}{\partial z} \right) \][/tex]

One way to check if [tex]\(\vec{F}\)[/tex] is conservative is to verify that the curl of [tex]\(\vec{F}\)[/tex] is zero:
[tex]\[ \nabla \times \vec{F} = \vec{0} \][/tex]

Given:
[tex]\[ \vec{F}(x, y, z) = \langle 4x - 2y + 2z, -2x + 2yz + z^2, 2x + 2yz + y^2 \rangle \][/tex]

We compute the curl [tex]\(\nabla \times \vec{F}\)[/tex]:

[tex]\[ \nabla \times \vec{F} = \left( \frac{\partial R}{\partial y} - \frac{\partial Q}{\partial z}, \frac{\partial P}{\partial z} - \frac{\partial R}{\partial x}, \frac{\partial Q}{\partial x} - \frac{\partial P}{\partial y} \right) \][/tex]

Calculate each component:

1. [tex]\(\frac{\partial R}{\partial y} - \frac{\partial Q}{\partial z}\)[/tex]:
[tex]\[ \frac{\partial}{\partial y} (2x + 2yz + y^2) = 2z + 2y \][/tex]
[tex]\[ \frac{\partial}{\partial z} (-2x + 2yz + z^2) = 2y + 2z \][/tex]
[tex]\[ \frac{\partial R}{\partial y} - \frac{\partial Q}{\partial z} = (2z + 2y) - (2y + 2z) = 0 \][/tex]

2. [tex]\(\frac{\partial P}{\partial z} - \frac{\partial R}{\partial x}\)[/tex]:
[tex]\[ \frac{\partial}{\partial z} (4x - 2y + 2z) = 2 \][/tex]
[tex]\[ \frac{\partial}{\partial x} (2x + 2yz + y^2) = 2 \][/tex]
[tex]\[ \frac{\partial P}{\partial z} - \frac{\partial R}{\partial x} = 2 - 2 = 0 \][/tex]

3. [tex]\(\frac{\partial Q}{\partial x} - \frac{\partial P}{\partial y}\)[/tex]:
[tex]\[ \frac{\partial}{\partial x} (-2x + 2yz + z^2) = -2 \][/tex]
[tex]\[ \frac{\partial}{\partial y} (4x - 2y + 2z) = -2 \][/tex]
[tex]\[ \frac{\partial Q}{\partial x} - \frac{\partial P}{\partial y} = -2 - (-2) = 0 \][/tex]

Since all components of the curl are zero, [tex]\(\nabla \times \vec{F} = \langle 0, 0, 0 \rangle\)[/tex]. Thus, [tex]\(\vec{F}\)[/tex] is conservative.

---

### Step 2: Find the Potential Function [tex]\(f(x, y, z)\)[/tex]

Since [tex]\(\vec{F}\)[/tex] is conservative, there exists a potential function [tex]\(f(x, y, z)\)[/tex] such that:
[tex]\[ \vec{F} = \nabla f \][/tex]

We need to find [tex]\(f\)[/tex] such that:
[tex]\[ \nabla f = \left( \frac{\partial f}{\partial x}, \frac{\partial f}{\partial y}, \frac{\partial f}{\partial z} \right) = \left( 4x - 2y + 2z, -2x + 2yz + z^2, 2x + 2yz + y^2 \right) \][/tex]

Integrate the first component with respect to [tex]\(x\)[/tex]:
[tex]\[ \frac{\partial f}{\partial x} = 4x - 2y + 2z \implies f(x, y, z) = 2x^2 - 2xy + 2xz + g(y, z) \][/tex]

Here, [tex]\(g(y, z)\)[/tex] is a function of [tex]\(y\)[/tex] and [tex]\(z\)[/tex] because the derivative with respect to [tex]\(x\)[/tex] should not change [tex]\(g(y, z)\)[/tex].

Integrate the second component with respect to [tex]\(y\)[/tex]:
[tex]\[ \frac{\partial f}{\partial y} = -2x + 2yz + z^2 \implies f(x, y, z) = -2xy + y^2z + z^2y + h(x, z) \][/tex]

Combining and resolving the terms, we assume consistent forms:
[tex]\[ f(x, y, z) = 2x^2 - 2xy + 2xz + y^2z + z^2y \][/tex]

Thus, potential function [tex]\( f \)[/tex] is:
[tex]\[ f(x, y, z) = 2x^2 - 2xy + 2xz + y^2z + z^2y \][/tex]

---

### Step 3: Evaluate the Potential Function at the Endpoints

Evaluate [tex]\( f \)[/tex] at [tex]\((1, 0, 2)\)[/tex]:
[tex]\[ f(1, 0, 2) = 2(1)^2 - 2(1)(0) + 2(1)(2) + (0)^2(2) + (2)^2(0) = 2 + 4= 6 \][/tex]

Evaluate [tex]\( f \)[/tex] at [tex]\((1, 1, 1)\)[/tex]:
[tex]\[ f(1, 1, 1) = 2(1)^2 - 2(1)(1) + 2(1)(1) + (1)^2(1) + (1)^2(1) = 2-2+2 +1+1 = 4 \][/tex]

---

### Step 4: Calculate the Line Integral

Using the Fundamental Theorem of Line Integrals:
[tex]\[ \int_C \vec{F} \cdot d\vec{r} = f(1, 1, 1) - f(1, 0, 2) \][/tex]

Thus,
[tex]\[ \int_C \vec{F} \cdot d\vec{r} = 4 - 6 = -2 \][/tex]

Final Answer:
[tex]\[ \boxed{-2} \][/tex]
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.